Automatic material wrapping equipment for salted duck egg production and processing - ZHA ANCHUN; LIANG YONG; ZHU WANJING; YIN HENGBING; ZHANG WANLIN; CHEN JING (2024)
The invention provides automatic material wrapping equipment for salted duck egg production and processing, and belongs to the field of duck egg processing, the automatic material wrapping equipment comprises an inclined seat, a material barrel is fixedly connected to the inclined seat, an annular frame is fixedly connected to one side of the top of the material barrel, and an inclined plate is fixedly connected to the front side of the annular frame; and the material moving assembly comprises a U-shaped frame fixedly connected to one side of the bottom of the material barrel, a motor is fixedly connected to the U-shaped frame, a rotating shaft is fixedly connected to the output end of the motor, abutting blocks are fixedly connected to the left side and the right side of the outer side of the rotating shaft correspondingly, and connecting rods are fixedly connected to the front side and the rear side of the outer side of the rotating shaft correspondingly. According to the duck egg wrapping machine, through